Broccoli sprouts as an underrated functional food: a rich source of bioactive compounds with prominent anticancer properties - Smala, Kamila; Głowacz, Julia; Popiel, Michał; Stanibuła, Dominik; Dziekoński, Kamil; Rybowski, Jakub; Wiśniowski, Maksymilian; Kulig, Klaudia (Quality in Sport, 2025)
Introduction: Broccoli sprouts, the young shoots of Brassica oleracea, are rich in sulforaphane (SFN), a bioactive compound with strong antioxidant and chemopreventive properties. SFN helps reduce oxidative stress, detoxify carcinogens, and regulate cellular pathways linked to cancer development. Other compounds present, such as polyphenols and glucosinolates, further enhance their health benefits. Due to their accessibility and high SFN content, broccoli sprouts are gaining attention as a complementary strategy in cancer prevention. Aim: This study aims to review current evidence on the anticancer properties of broccoli sprouts, focusing on SFN’s mechanisms in cancer prevention and therapy, including its role in cellular defense, apoptosis, and epigenetic regulation. Materials and Methods: A literature review was conducted using PubMed, Scopus, and Google Scholar, covering studies from 2015 to 2025. Research on the effects of SFN in preclinical models, human trials, and epidemiological studies was analyzed. Both in vitro and in vivo studies were evaluated to assess SFN’s relevance to human cancer prevention and treatment. Results: SFN shows anticancer activity through activation of the Nrf2 pathway, induction of apoptosis, and modulation of the cell cycle. Preclinical and in vitro studies report reduced tumor growth, suppressed proliferation, and enhanced detoxification. SFN also influences gene expression through epigenetic mechanisms. While clinical data are limited, early evidence supports a role for broccoli sprouts in reducing cancer risk. Conclusions: Broccoli sprouts offer strong potential as a functional food in cancer prevention, thanks to their SFN content and multifaceted biological effects. Further clinical research is needed to confirm efficacy, dosage, and safety in humans. Their affordability and availability make them a promising tool for public health.